Shared Secrets : The Queer World of Newbery Medalist Charles J. Finger - Shores, Elizabeth Findley (Book collections on Project MUSE., 2021)
"Biography of the British expatriate Charles Joseph Finger (1867-1941), known primarily as an award-winning author of children's literature. Finger's allusive and suggestive short fiction won some critical acclaim during his lifetime, but the Newbery Medal that made him famous ended his development as an author of serious queer literature. His insistence on forging a life on the secret byways of queer culture offers a rare example of gay community at a time when openly lived identities were prohibitively difficult to actualize"--